Enhanced-throughput multipath routing algorithm based on network coding in IoVs - Cun-qun FAN; Shang-guang WANG; Wen-zhe GU; Qi-bo SUN; Fang-chun YANG (Tongxin xuebao)
In Internet of Vehicles (IoVs), the frequent interruptions of wireless links between the vehicles cause data retrans-mission, which makes the whole vehicle network performance fall sharply. Hence, a multipath routing algorithm was pro-posed for enhancing throughput. The core of the algorithm is to make the vehicle clustering algorithm support network cod-ing, which can achieve the purpose of recovery of disorder and lost packets. Firstly, a collaborative coding communication model was established to achieve mutual cooperative multi-path transmission between vehicle nodes in the same cluster. Secondly, network linear coding was adopted to encode the transmitted data of source vehicle nodes and intermediate vehicle nodes. Finally, destination nodes decode the received data. The performances of the scheme were evaluated by QualNet software. Simulation results show that the algorithm could effectively improve the throughput of multi-path routing in IoVs.